Prospective seroepidemiological study of human toxocarosis in Bahia Blanca, Buenos Aires province, Argentina - Costamagna, Sixto Raúl (2012)
The Inhabitants of Villa Nocito neighbourhood in Bahia Blanca, Buenos Aires Province, Argentina, suffers from many basic needs. In earlier studies, the authors have shown that 2.7% of dog feces collected in public places in the area had Toxocara canis eggs. In this paper, T. canis antibody prevalence is studied in sera from 94 local inhabitants of different ages and both sexes. Two ELISA tests were employed -LMD Toxocara Serology and a laboratory-made one. The Immuneblotting Technique (WB) was used as confirmatory test. Statistical analysis was performed with Fisher Test and EPIDAT 3.1, 2006 software. Results showed 18% seroprevalence for T. canis. Mean sensitivity of ELISA tests was 96.79% with 86.55% of predictive value of positive result, without any significant differences between the two when compared with WB. No statistical significant risk associations were detected for sex, age, current water use, type of bathroom, contact with animals and earth, journeys, parasitosis history, and presence of special signs or symptomatology. Even though positive serology percentage was higher among those who had cesspit to dispose feces, this fact did not show a statistical significant difference (p: 0,14). Results showed a lower seroprevalence for T. canis than other authors have reported in 1994 and are in agreement with the scarce presence of T. canis eggs in feces of local dogs.